Why is suicide a social problem? - Jonatan Baños Chaparro (Medisur)
Suicide is a persistent social and public health problem; every year represents a global crisis that affects contemporary societies. A dominant psychopathological perspective summarizes current understanding. However, empirical evidence suggests that suicide is a complex, ambivalent and multidimensional phenomenon, involving social, economic, cultural and educational aspects. Every death by suicide is a failure of society and public policies. The purpose of this work is to offer some reasons to conceptualize suicide as a social problem.